2010
DOI: 10.1086/652009
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Energy Distributions of Be and Other Massive Stars

Abstract: ABSTRACT. We present spectrophotometric data from 0.4 μm to 4.2 μm for bright, northern sky, Be stars and several other types of massive stars. Our goal is to use these data with ongoing high-angular-resolution interferometric observations to model the density structure and sky orientation of the gas surrounding these stars. We also present a montage of the Hα and near-infrared emission lines that form in Be star disks. We find that a simplified measurement of the IR excess flux appears to be correlated with t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 47 publications
(62 reference statements)
3
8
0
Order By: Relevance
“…Lenorzer et al (2002) examined the ISO spectra of this star and found that their line intensity ratios were closer to the optically thick case, implying opaque lines and a disk-like envelope. Touhami et al (2010) also reported an infrared spectrum of γ Cas, with similar characteristics to those mentioned by previous authors.…”
Section: The Sample Of Be Starssupporting
confidence: 85%
See 2 more Smart Citations
“…Lenorzer et al (2002) examined the ISO spectra of this star and found that their line intensity ratios were closer to the optically thick case, implying opaque lines and a disk-like envelope. Touhami et al (2010) also reported an infrared spectrum of γ Cas, with similar characteristics to those mentioned by previous authors.…”
Section: The Sample Of Be Starssupporting
confidence: 85%
“…Infrared spectroscopic studies of Be stars have shown that some of these spectra display plenty of hydrogen emission lines that are a result of recombination processes. Particularly, in the L-band, centered in 3.5 μm, there are notorious emission lines of Brackett, Pfund, and Humphreys hydrogen series (Sellgren & Smith 1992;Hony et al 2000;Lenorzer et al 2002;Mennickent et al 2009;Granada et al 2010;Touhami et al 2010). Mennickent et al (2009) obtained L-band spectra of 13 outbursting Be stars through use of the ISAAC/VLT facility, with a resolving power of 1200.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We caution that the estimates in Table 1 do not account for the possible added flux from disks around both components. Be star disks produce a continuum excess that grows with wavelength and may change the flux from the Be star and its decretion disk by as much as 0.3 mag in the H band (Touhami et al 2010). This would increase the magnitude difference between the Be star and its companion by the same amount.…”
Section: Formation Modelsmentioning
confidence: 99%
“…The infrared excesses are believed to originate in the densest region of the disk near the star and in and near the equatorial plane (Touhami et al 2010). Therefore, since the hydro-on models provide a self-consistent density and temperature distribution, especially important for the densest regions, the hydro-on models are expected to provide a more realistic representation of the physical conditions in the dense gas.…”
Section: Disk Density Models 431 Spectral Group B0mentioning
confidence: 99%